Energy-Model-Based Optimal Communication Systems Design for Wireless Sensor Networks. (19th December 2012) - Li, Ye; Qiao, Dengyu; Xu, Zhao; Xu, Da; Miao, Fen; Zhang, Yuwei
Abstract : As is widely used in our daily life, wireless sensor network (WSN) is considered as one of the most important technologies of the new century. Although, the sensor nodes are usually battery powered with limited energy sources, the system energy consumption must be minimized in order to extend the life time. Since the energy consumption of transceiver front ends is dominant in the whole sensor nodes, we focus on how to minimize energy consumption by the system level design. According to the applications, we analyze four types of RF architectures: on-off keying (OOK) transceiver, phase-shift keying (PSK) transceiver, quadrature amplitude modulation (QAM) transceiver, and frequency-shift keying (FSK) transceiver which are widely used in WSN and establish the related energy models for each kind of architecture, respectively. We connect the baseband parameters such as modulation level, data rate, bandwidth, and propagation distance. with the energy consumption of RF front end for WSN. Afterwards, through theoretical and numerical analysis in system level, we discuss and conclude how to design optimal energy-quality system in terms of various application scenarios.